2022
DOI: 10.3389/fphys.2022.959747
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor-associated macrophages in oral squamous cell carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a common head and neck cancer with a high recurrence rate and a low 5-year survival rate. Tumor-associated macrophages (TAMs) are important immune cells in the tumor microenvironment, which play an important role in the progression of many tumors. This article reviews the origin, and the role of TAMs in the invasion, metastasis, angiogenesis and immunosuppression of OSCC. Therapeutic strategies targeting TAMs are also discussed in hopes of providing new ideas for the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…The potential roles of T cells and macrophages in antitumor responses have been well-determined in many previous studies. In some human cancers, negative correlations have been reported between the number of infiltrating T cells and macrophages and the histological severity of the tumor [ 9 , 18 , 27 ]. A decrease in T cells in the mucous stroma has been reported [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential roles of T cells and macrophages in antitumor responses have been well-determined in many previous studies. In some human cancers, negative correlations have been reported between the number of infiltrating T cells and macrophages and the histological severity of the tumor [ 9 , 18 , 27 ]. A decrease in T cells in the mucous stroma has been reported [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 50 , 51 ] Currently, there are many research targets related to TAMs, including colony stimulating factor 1, Pexidartinib, Sotuletinib, Emactuzumab, and so on. [ 52 , 53 ] Despite the increasing research on TAMs, there are still many unknowns about their role in the genesis, regulation, and treatment of HNSCC, which need to be explored by more studies. In conclusion, TAMs are an attractive target for HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor‐associated macrophages (TAMs) are one of the most abundant immune cells in TME. TAMs play a key role in tumor proliferation, migration, and angiogenesis, and can inhibit the killing effect of T cells and NK cells on tumor cells, thus promoting tumor cells to evade the immune surveillance 24 . TAMs have strong functional plasticity, which could be acquired as immunostimulatory (M1‐like) or immunosuppressive (M2‐like) abilities, and more various functional phenotypes in between of M1‐like with M2‐like 25 .…”
Section: Interactions Between Exosomes and Osccmentioning
confidence: 99%
“…TAMs play a key role in tumor proliferation, migration, and angiogenesis, and can inhibit the killing effect of T cells and NK cells on tumor cells, thus promoting tumor cells to evade the immune surveillance. 24 TAMs have strong functional plasticity, which could be acquired as immunostimulatory (M1-like) or immunosuppressive (M2-like) abilities, and more various functional phenotypes in between of M1-like with M2-like. 25 Xiao et al found that macrophages were activated to be M1-like TAMs by conditioned culture medium derived from OSCC cells, and a novel paracrine ring between cancer cells and macrophages was proposed based on OSCC-derived exosomes.…”
Section: Exosomes Mediated Immune Effects On Osccmentioning
confidence: 99%